Non-covalent Interactions of Graphene with Polycyclic Aromatic Hydrocarbons - Zygouri, Panagiota; Potsi, Georgia; Mouzourakis, Eleftherios; Spyrou, Konstantinos; Gournis, Dimitrios; Rudolf, Petra (Current Organic Chemistry, 2015)
In this mini review we discuss the interactions of polyaromatic hydrocarbons (PAHs) with graphene and the experimental approaches developed so far to create novel graphene/PAH hybrids and composite systems. The utilization of these systems in electrical, biomedical and polymer-reinforcement applications is described while special emphasis is given to environmental remediation issues.
Keywords: polycyclic aromatic hydrocarbons